Prevalence of hepatitis E virus antibodies in individuals exposed to swine in Mato Grosso, Brazil - Sabrina Monteiro Tosoncin da Silva; Jacqueline Mendes de Oliveira; Cláudia Lamarca Vitral; Karina de Almeida Vieira; Marcelo Alves Pinto; Francisco José Dutra Souto (Memorias do Instituto Oswaldo Cruz, 2012)
This study was conducted to estimate the prevalence of hepatitis E antibodies (anti-HEV) among individuals exposed to swine in the rural areas of the state of Mato Grosso (MT) in Brazil. The study included 310 participants who had an average age of 39 years. Fifty-one per cent of the participants were female and 26 (8.4%) were anti-HEV-positive. Concomitantly, we studied 101 blood donors from the urban area of the state capital who had never lived in a rural area or handled swine. Four per cent (4%) of these individuals were anti-HEV-positive (p = 0.206). When we compared the anti-HEV-positive participants who had been exposed to swine with the anti-HEV-negative participants, we noticed associations between the presence of anti-HEV and increased age, a history of blood transfusions and contact with other farm animals. However, after a multivariate analysis was performed, this association was not confirmed. Finally, the ratio of anti-HEV-positive individuals who had been exposed to swine in rural MT was similar to that found in previous studies in Brazil. This prevalence did not characterise this type of exposure as a risk factor for HEV infection in this region.